To the issue of developing working land management projects to improve the condition of agricultural land and protect land from erosion in Ukraine - Koshel, A.; Kolhanova, I.; Kempa, O.; Stacherzak, A. (Land Management, Cadastre and Land Monitoring, 2023)
Abstract. Scientific and methodical approaches to the development of working land management projects for improving the condition of agricultural land and protecting land from erosion are proposed.The main reasons for the emergence and active development of erosion processes are the irrational destruction of natural vegetation, the deterioration of the infiltration and water-absorbing capacity of soils and their anti-erosion resistance. Modern soil erosion is mainly related to human agricultural activities. But in the absence of protective measures, it also develops in the territories of settlements and industrial enterprises, road routes, etc. Therefore, a planned and effective war against erosion is an integral part of the entire system of anti-erosion organization of the territory, and should include such basic measures as: organizational and economic, agrotechnical, forest improvement, hydrotechnical, which must interact, be designed and implemented in harmony with each other.The obtained results can be used in the development of working land management projects and the implementation of comprehensive measures to improve the condition of the land and protect the soil from erosion.Keywords: erosion, working project of land management, disturbed lands, soil protection, fertile soil layer, unproductive lands, land management documentation, land management, management, land use.
Keywords: erosion; working project of land management; disturbed lands; soil protection; fertile soil layer; unproductive lands; land management documentation; land management; management; land use.